The Modernization of Sa’lakaa and the Sa’lakaa of Modernity (Contemporary Poetry as a Model) - Feyzoleslam, Jahad (Journal of Arabic Language Sciences and Literature, 2022)
The phenomenon of misery and what results from it is a preoccupation for many researchers in different countries of the world, especially in societies and governments with bad economies, where the problem becomes more complex. The research addresses the study of the contemporary and the current troubled era in the vision and thought of the poets who were ravaged by this phenomenon with its deadly storms and cyclones and the reflection of the distressed societies on their poetry and its impact on their souls and literary experiences, and then comparing this phenomenon with the troubled era of some past eras, including the tangible results of the ignorant era and its productive era. In societies with limited income, as well as in which misery and tyranny are rampant, this deadly beast draws the attention and attention of those concerned with human humanity. In fact, there has been a long debate about al- Salqa poetry and the value of studying this literary, social, and economic phenomenon and its feasibility on literature and poetry and its impact on human society, which calls for contemplation and careful consideration of its causes and causes and the treatment poets for it.